2019
DOI: 10.29333/aje.2019.413a
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Differentiated Instruction: Conjoint Effect of Teachers’ Sense of Efficacy, Perception and Knowledge

Abstract: Existing literature suggests that teachers' sense of efficacy, their perception and knowledge of differentiated instruction (DI) are related to their implementation of differentiation. However, there is deficiency of research examining the predictive nature of those relationships. The purpose of this study is to examine the impact of teachers' perception and knowledge of differentiated instruction, and their sense of teacher efficacy on the implementation of DI strategies. The study employed a tool composed of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…According to Tomlinson and Imbeau (2010), it is because teachers lack the competence to diversify instruction that they may not use DI. Moreover, time and resource constraints, large class sizes, lack of administrative support, commitment, and motivation all play a role in making DI challenging to implement (Melesse, 2015;Mengistie, 2020;Moosa & Shareefa, 2019a;Suprayogi et al, 2017) and have all been identified as the major constraints that lead to teachers' low perceptions of DI (Nicolae, 2014;Tomlinson & Imbeau, 2010). According to Merawi (2018), as student diversity grows and resources become scarce, teachers' perceptions of DI and its implementation might be overwhelming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Tomlinson and Imbeau (2010), it is because teachers lack the competence to diversify instruction that they may not use DI. Moreover, time and resource constraints, large class sizes, lack of administrative support, commitment, and motivation all play a role in making DI challenging to implement (Melesse, 2015;Mengistie, 2020;Moosa & Shareefa, 2019a;Suprayogi et al, 2017) and have all been identified as the major constraints that lead to teachers' low perceptions of DI (Nicolae, 2014;Tomlinson & Imbeau, 2010). According to Merawi (2018), as student diversity grows and resources become scarce, teachers' perceptions of DI and its implementation might be overwhelming.…”
Section: Discussionmentioning
confidence: 99%
“…For effective teaching, having a positive perception is vital. Teachers' perceptions and beliefs towards their students and teaching have a significant impact on students' academic performance and their practices (Merawi, 2018;Moosa & Shareefa, 2019a). Guskey (2002) stated that perceptions and beliefs about teaching are often primarily derived from classroom practices and experiences.…”
Section: Differentiated Instructionmentioning
confidence: 99%
“…The ones with advanced learning abilities sit next to the students who might struggle with using the language. That diversity of students' characteristics demands teaching strategies that can cater to the various mixability in a classroom (Moosa & Shareefa, 2019). Therefore, researchers and policy-makers need teachers to embrace diversity and adapt their instruction to the diverse learning process based on the needs of students in their class.…”
Section: The Implementation Of Teaching English Using Differentiated ...mentioning
confidence: 99%
“…However, on the contrary, the implementation of differentiated instruction on processes based on students' readiness levels was not visible. Differentiating process based on students' readiness level refers to matching the task's complexity based on materials and support to a student's current level of knowledge, understanding, and skill (Moosa & Shareefa, 2019). In the process of making sense of the idea they just learned, the teacher did not design any activities in which students work with a different task based on their readiness level.…”
Section: The Implementation Of Differentiated Instructionmentioning
confidence: 99%
“…At the classroom level, teachers' pedagogical content knowledge (PCK) accounts for the quality of instruction (Baier et al, 2019;Depaepe et al, 2020;Sorge et al, 2019). Pedagogical content knowledge is indispensable in implementing the science curriculum (Moosa & Shareefa, 2019;Suh & Park, 2017). Similarly, science teachers should be supported by extensive, transformative, and continuing professional development to effectively implement any curriculum reform (Madani & Forawi, 2019;Mamlok-Naaman, 2017;Marshall et al, 2017).…”
Section: Introductionmentioning
confidence: 99%